The Effect of Financial Literature and Attitude on The Behavior of Financial Management of The Young Generations of Bangka Belitung - Sumiyati (Universitas Teknologi Yogyakarta, 2021)
The knowledge of young people in financial management must be better than that of the older generation. With the knowledge that is owned and the development of science and technology today there is no reason to make the young generation go bankrupt on campus. This study aims to see the effect of financial literacy and financial attitudes on financial management behavior in creating young people in Bangka Belitung. This research is a quantitative research with a survey approach. The survey was conducted on students of the Faculty of Economics, University of Bangka Belitung with a total of 169 respondents. The survey was conducted through distributing online questionnaires (google form) and multiple regression analysis was used to test the hypothesis. The results showed that financial literacy and influence on financial management behavior. This shows that creating young people who have good financial literacy skills and a rational attitude in managing their finances in the future.